Predictors of scoring accuracy: Ice hockey wrist shot mechanics - Michaud-Paquette, Y.; Pearsall, D. J.; Turcotte, R. A.; Covo, K. (2008 Annual Meeting (NACOB) Ann-Arbor, 2008)
In the sport of ice hockey the stick is used to control and shooting the puck (hard rubber cylindrical disk) while points gained by scoring (i.e. putting the puck in opposing team`s net The wrist shot is generally accepted as a more accurate technique for puck projection1. There has been little attempt to compare the stick behavior with the performance outcome during shooting. In throwing or striking tasks, the projection angle and velocity release are crucial for the accuracy outcome. The purpose of this study is to identify the kinematics patterns of the ice hockey stick from a wrist shot that correspond to the accuracy of puck trajectory.